2006
DOI: 10.1080/00365590600795222
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral RollerLoop vapor resection of prostate for treatment of symptomatic benign prostatic hyperplasia: A 2-year follow-up study

Abstract: Our results suggest that TUVRP provides equivalent safety and efficacy to TURP during a 2-year follow-up period, in which short-term advantages in perioperative morbidity and cost savings were also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…After PKEP [62,102,103], the risk of RE increased from baseline but did not reach statistical significance ( = 0.06). The pooled analysis of two studies on transurethral vaporization resection of the prostate (TUVRP) [40,82] showed a significant higher risk of RE also for this procedure (RR 70.94; 95% CI 9.99, 503.62; p < 0.0001). Overall, the other electrosurgical group showed a significantly higher risk of RE compared with baseline (RR 34.77; 95% CI 10.58, 127.82; p < 0.00001).…”
Section: Retrograde Ejaculationmentioning
confidence: 99%
“…After PKEP [62,102,103], the risk of RE increased from baseline but did not reach statistical significance ( = 0.06). The pooled analysis of two studies on transurethral vaporization resection of the prostate (TUVRP) [40,82] showed a significant higher risk of RE also for this procedure (RR 70.94; 95% CI 9.99, 503.62; p < 0.0001). Overall, the other electrosurgical group showed a significantly higher risk of RE compared with baseline (RR 34.77; 95% CI 10.58, 127.82; p < 0.00001).…”
Section: Retrograde Ejaculationmentioning
confidence: 99%